Five new records and morphological data of polyclad species (Platyhelminthes: Turbellaria) from Rio Grande do Norte, Northeastern Brazil - Bahia, Juliana; Padula, Vinicius; Delgado, Marlon (Zootaxa, 2012)
In Brazil, 66 flatworm species of the order Polycladida are known, most of which collected from the southeastern Braziliancoast. The present study includes morphological descriptions of five species from Rio Grande do Norte State, BrazilianNortheastern coast: Enchiridium evelinae, Phrikoceros mopsus, Pseudobiceros evelinae, Thysanozoon brocchii and Hop-loplana divae. These findings represent the first record of Polycladida for this region of Brazil. Also, for the first timeEnchiridium evelinae, Pseudobiceros evelinae and Hoploplana divae are illustrated with color photographs of live spec-imens and histological details. Association with compound ascidians and encrusting bryozoan were observed and com-mented. Our data suggest that knowledge about Brazilian polyclads is underestimated and emphasizes the necessity of further studies to better understand the Polycladida biodiversity in Brazil.